The Owner Factor: An Innovation Element of Business Model Canvas by SMEs Rattan Industry in Cirebon Indonesia - Ida Hindarsah , Bambang Heru Purwanto , Sidiq Priadana and Adi Fahrudin (International Journal of Advanced Science and Technology, 2020)
Indonesia is the largest rattan producing country in the world. It is estimated that 80%of rattan raw material worldwide is produced by Indonesia, the rest is produced by othercountries such as the Philippines, Vietnam and other Asian countries. In 2003-2006 therattan industry in Indonesia experienced ups and downs with an average of 0.38% perannum and a decrease of an average of - 3.63% per year. Most of the rattan industryplayers are from West Java Province, to be exact from Cirebon. Small MediumEnterprises (SMEs) is one of the actor of this trading industry. Although some SMEs areexperiencing collapsed due to intense competition in the globalization era. Nevertheless,there are still several SMEs that can survive to this day. So in this connection, thequestion arises of business model innovations such as what is done by rattan SMEs inCirebon Regency in facing business competition in the globalization era? This paperusing qualitative method to describe the innovation components applied by SMEs. Theresult shows that rattan industry SMEs in Cirebon Regency based on BMC approach theyapplied all the components and one component plus that is owner predisposing factorwhich is the basic behavior of the owner that will influence the application of the entirecomponent of business model.